An introduction to the why and how of risk adjustment. Issue 1 (1st January 2020) - Vogel, W. Bruce; Chen, Guoqing John
Abstract : Department of Veterans Affairs (VA) health services researchers often adjust for the differing risk profiles of selected patient populations for a variety of purposes. This paper explains the major reasons to conduct risk adjustment and provides a high level overview of what risk adjustment actually does and how the results of risk adjustment can be used in different ways for different purposes. The paper also discusses choosing a diagnostic classification system and describes some of the systems commonly used in risk adjustment along with comorbidity/severity indices and individual disease taxonomies. The factors influencing the choice of diagnostic classification systems and other commonly used risk adjustors are also presented along with a discussion of data requirements. Statistical approaches to risk adjustment are also briefly discussed. The paper concludes with some recommendations concerning risk adjustment that should be considering when developing research proposals.